Hambatan dalam Mempertahankan Eksistensi Pelaku Usaha Ekonomi Kreatif di Desa Wisata Sengigi Kabupaten Lombok Barat - Oktiani, Asri; Permadi, I Gusti Agung Didit Eka; Zakaria, Ahmad; Fikri, Modh. Haikal (LPPM Institut Pendidikan Nusantara Global, 2025)
This study investigates the challenges faced by creative economy actors in Senggigi Tourism Village, West Lombok Regency, in maintaining their business sustainability. The background of this research stems from the decline in tourist visits following the 2018 earthquake, the Covid-19 pandemic, and the rise of competing destinations such as the Mandalika Special Economic Zone. These conditions have significantly impacted the continuity of local creative businesses. A descriptive qualitative method with a case study approach was employed. Data were collected through interviews, observations, and documentation involving actors in the creative economy. The data were then analyzed using thematic analysis and the fishbone diagram to identify the root causes of the problems. The findings show that internal challenges include limited product innovation, uncompetitive pricing, restricted distribution channels, insufficient digital promotion, inconsistent service processes, weak branding, and inadequate managerial and foreign language skills. External challenges include natural disasters, pandemics, competition from modern destinations, shifting tourist preferences, inadequate government support, limited access to financing, and underutilization of technology and networks. This study finds that Senggigi’s creative economy can thrive by embracing its unique culture, innovating products, ensuring fair prices and quality, and connecting more with stakeholders. Strong business management, skilled people, and digital marketing will help meet global challenges. The study’s results show how the 7P marketing mix applies to tourism, and provide clear steps Senggigi Tourism Village can take to stand out in the world.